(untitled) (GEOMATE Journal, 2025)
This study examines the growth dynamics and structure of an uneven-aged pure Scots pine (Pinus sylvestris) stand in the alpine zone at elevations between 1800 and 2200 meters in Georgia, with the forest ending at 2188 meters. The research site was centered at 2056 meters, where a one-hectare plot was selected. To avoid edge effects, we chose a denser part of the forest rather than the border, ensuring natural resource distribution. Data on tree height, diameter at breast height (DBH), and annual growth increments were collected from a randomly selected plot. Dendrochronological analysis showed younger trees (<40 years) had a mean growth rate of 1.588 mm/year (±0.1505 mm) over five years, while trees aged 40–70 years and over 70 years exhibited rates of 1.173 mm/year (±0.0723 mm) and 1.166 mm/year (±0.2245 mm), respectively. Findings highlighted correlations between age, height, and DBH, showing distinct growth patterns tied to tree age and size. The uneven-aged structure influenced light availability and competition, impacting growth rates. Regeneration analysis revealed diverse age distribution, suggesting ongoing recruitment. Relationships between DBH increment and average DBH indicated faster growth until trees reached a specific size threshold. These insights enhance understanding of growth processes in uneven-aged pine stands, with implications for sustainable forest management. Findings on growth dynamics and recruitment patterns can guide conservation strategies, balancing forest productivity with ecosystem health.